1986
DOI: 10.1021/jm00156a026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of resolved carbon-10 diastereomers of 10-methyl- and 10-ethyl-10-deazaminopterin

Abstract: Synthesis and evaluation of the antitumor drugs 10-methyl- and 10-ethyl-10-deazaminopterin (15a,b) were previously reported for the diastereomeric mixtures, lacking resolution at the C-10 position. In order to assess biological properties of the individual diastereomers, the C-10 isomers of 4-amino-4-deoxy-10-methyl- and 10-ethyl-10-deazapteroic acids (13a,b) were prepared by total synthesis. Coupling with L-glutamate afforded the appropriate diastereomers of the title compounds. Biochemical, transport, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Because of the chiral nature of C-10 in 16 and 17 , these compounds can exist as mixtures of diastereomers, as is also true for 10-methyl-10-deazaaminopterin and edatrexate . Our 500-MHz 1 H NMR spectra indicate that both diastereomers are in fact present in 16 and 17 in roughly equal proportions, so that the IC 50 values in Table actually represent the averaged contributions of the 10 R and 10 S isomers.…”
Section: Biological Activitymentioning
confidence: 66%
See 1 more Smart Citation
“…Because of the chiral nature of C-10 in 16 and 17 , these compounds can exist as mixtures of diastereomers, as is also true for 10-methyl-10-deazaaminopterin and edatrexate . Our 500-MHz 1 H NMR spectra indicate that both diastereomers are in fact present in 16 and 17 in roughly equal proportions, so that the IC 50 values in Table actually represent the averaged contributions of the 10 R and 10 S isomers.…”
Section: Biological Activitymentioning
confidence: 66%
“…Three different approaches to the synthesis of 10-deaza analogues of 2 were investigated (Schemes −4). In general, these approaches are patterned after routes used previously to obtain the corresponding glutamate analogues. Thus, as shown in Scheme , coupling of 4-formylbenzoic acid ( 22 ) to methyl 2- l -amino-5-phthalimidopentanoate hydrochloride ( 23 ·HCl) 17 via the mixed carboxylic anhydride (MCA) method afforded aldehyde 24 . The latter was used in a Wittig reaction with the putative 2,4-bis(phosphazene) ylide 25 , , arising either from pre-formed 2,4-diamino-6-(bromomethyl)pteridine hydrobromide ( 26 ·HBr) or in situ from 2,4-diamino-6-(hydroxymethyl)pteridine ( 27 ) as we described earlier .…”
Section: Chemistrymentioning
confidence: 99%
“…Similar substitutions of a methyl group in the C9-C10 bridge region of 6-6 fused analogues have been reported by DeGraw et al . ,11a,b in 2,4-diaminopteridine and 2,4- diaminopyrido[2,3- d ]pyrimidine analogues which enhanced inhibitory activity against tumor cells in culture. As part of a structure−activity relationship (SAR) study on the relative conformational orientation of the furo[2,3- d ]pyrimidine ring with respect to the benzoylglutamate side chain of the two-atom bridged classical 2,4-diamino-5-substituted-furo[2,3- d ]pyrimidine antifolates, we designed and synthesized N -[4-[1-methyl-2-(2,4-diaminofuro[2,3- d ]pyrimidin-5-yl)ethyl]benzoyl]- l -glutamic acid ( 5 ), the 9-methyl analogue of 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of classical antifolate C9-C10 bridged analogues have been reported in the 6-6 fused bicyclic sytems, such as pteridines, pyrido[2,3- d ]pyrimidines, , and pyrido[3,2- d ]pyrimidines, and C8-C9 bridged analogues in the 6-5 fused bicyclic systems, such as pyrrolo[2,3- d ]pyrimidines, cyclopenta[ d ]pyrimidines, and furo[2,3- d ]pyrimidines . There is however a dearth of information regarding the E - and Z -isomers of these C-C bridged classical analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling studies us-ing Sybyl 6.5 7 suggested that extending the C9-methyl to an ethyl moiety could further enhance both the hydrophobic interaction with the enzyme and increase the lipophilicity, which might provide more potent inhibition of the growth of tumor cells. Similar homologation of a methyl moiety to an ethyl in the C9-C10 bridge region of 6-6 fused bicylic analogues derived from deaza aminopterin (AMT) has been extensively studied [8][9][10][11] and led to the discovery of edatrexate, 10 the 10-ethyl-10-deaza AMT analogue, which was advanced to phase III clinical trials. DeGraw et al 11a,b reported that in the 10-alkyl-5,10-dideaza AMT analogues, homologation of the 10-methyl moiety to an ethyl increased its growth inhibitory potency against tumor cells in culture and, more importantly, alkylation of the Polyglutamylation via folylpolyglutamate synthetase (FPGS) is an important mechanism for trapping classical folates and antifolates within the cell thus maintaining high intracellular concentrations and in some instances for increasing the binding affinity for folatedependent enzymes.…”
Section: Introductionmentioning
confidence: 99%